2015
DOI: 10.1016/j.poly.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopic study of hydroxylpyromorphite Pb10(PO4)6OH2–hydroxylmimetite Pb10(AsO4)6(OH)2 solid solution series

Abstract: A total of seven compounds of the hydroxylmimetite Pb 10 (AsO 4) 6 (OH) 2hydroxylpyromorphite Pb 10 (PO 4) 6 (OH) 2 (HPY-HMI) solid solution series were synthesized at 80 °C from aqueous solutions and characterized using XRD, SEM-EDS and FTIR. The substitution effect of [PO 4 ] 3− anions by [AsO 4 ] 3− on systematic changes in lattice parameters and spectral properties has been explained based on correlation between chemical composition and the peak positions. The substitution results in systematic linear incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…The results of wet chemical analysis presented in Table 1 are in accordance with the intended composition of products of synthesis as well as with the EDS data [27]. Dutrizac [32] do not apply here.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The results of wet chemical analysis presented in Table 1 are in accordance with the intended composition of products of synthesis as well as with the EDS data [27]. Dutrizac [32] do not apply here.…”
Section: Resultssupporting
confidence: 79%
“…morphology, chemical composition and XRD patterns and crystal lattice parameters) are presented elsewhere [27]. Briefly, the samples were precipitated from aqueous solutions in [27]. In addition to the EDS data presented therein, the composition of the synthetic phases was determined by wet chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The current refinement of Pb 5 (AsO 4 ) 3 (OH) is based on the first single-crystal study and reports all atoms with anisotropic displacement parameters. The previously given unit cell parameters from room-temperature powder data are slightly larger than those of the current single-crystal study (Table 1): a = 10.154, c = 7.515 Å, V = 671.02 Å 3 [49]; a = 10.187, c = 7.523 Å, V = 676.303(13) Å 3 [22]; a = 10.14 (8), c = 7.50(1) Å, V = 669 Å 3 [50]. Unit cell parameters predicted from elemental radii using pattern recognition and artificial intelligence methods, a = 9.8939, c = 7.6039 Å, V = 644.617 Å 3 [51], are much smaller than all experimentally determined values.…”
Section: Pb 5 (Aso 4 ) 3 Ohcontrasting
confidence: 66%
“…Several chemical analyses of natural apatite supergroup minerals formed in the oxidation zone indicate that the elemental composition of apatites mirror the composition of the aqueous solutions from which they precipitate [18,20]. Several synthesis experiments have also shown that the composition of products can be accurately controlled by the composition of the initial solutions [11,17,[21][22][23][24][25][26][27][28]. Hence, induced apatite precipitation can be used to immobilize pollutants in contaminated soils, waste, or waters.…”
Section: Introductionmentioning
confidence: 99%